ANALISIS DEMAND FORECASTING DAN INVENTORY CONTROL PRODUK PALLET KAYU PADA CV ALTRUIST BATAM - Paryaningsih; Arsyad Sumantika (Computer Science and Industrial Engineering, 2025)
CV Altruist Batam is an agency engaged in the manufacture of wooden pallets that are in high demand from customers with various size variations such as wooden pallet products with a size of 120 cm x 80 cm. CV Altruist Batam should use aggregate forecasting and planning to plan the amount of production that will occur in the future according to production capacity so that this study aims to identify the best forecasting techniques and the best overall strategy that can be used in forecasting and production planning for wooden pallet products measuring 120 cm x 80 cm using the Single Moving Average and Single Exponential Smoothing methods. While for aggregate planning, the strategies used include Chase Strategy, Level Strategy and Mixed Strategy, then the most efficient strategy is selected to minimize production costs. The results of the study showed that the best forecasting method is the Single Moving Average method with the values obtained MAD = 94.36, MSE = 4.971% and for the aggregate strategy chosen is Level Strategy and Chase with the smallest production cost of Rp 3,092,670,000.